Exploring the Protective Effect of Ascorbic Acid and AqueousExtract of Spirulina platensison Methotrexate-Induced Lipid Peroxidation: Antioxidant effect of Spirulina platensis - Supratim Ray; Kunal Roy; Chandana Sengupta (Iranian Journal of Pharmaceutical Sciences, 2007)
This study was designed to explore the protective effects of ascorbic acid andwater extract of Spirulina platensis(blue green algae) on methotrexate-induced lipidperoxidation using goat liver as the lipid source. This in vitroevaluation was doneby measuring the malondialdehyde, 4-hydroxy-2-nonenal, reduced glutathione andnitric oxide content of tissue homogenates. The study reveals the lipid peroxidationinduction capacity of methotrexate, the anti-peroxidative potential of ascorbic acidand aqueous extract of S. platensison methotrexate-induced lipid peroxidation.